Consumer Behavior Evaluation Model for Marketing Tourist Destinations - Ángel, Lemoine; Zambrano, Gema; Hernández, Norma (American Journal of Business Science Philosophy, 2025)
The objective focused on designing a consumer behavior evaluation model to enhance the segmentation, positioning, and marketing of tourist destinations. The research employed both quantitative and qualitative methods, which facilitated the development of a model structured in three stages, using tools such as data analysis and specialized software. The sample consisted of 366 tourists, selected through random convenience sampling. Surveys conducted with tourists revealed a majority profile of young and middle-aged men with a high level of education and middle-class background, primarily seeking relaxation, recreation, and cultural experiences. Most expenses were directed toward food and accommodation. The conclusions suggest that, to close the gap between actual and desired behavior, it is necessary to improve the tourism offerings and align services and infrastructure with visitors' expectations to increase satisfaction and destination competitiveness. The proposed model aims to evaluate consumer behavior and design actions that improve the economic and commercial performance of tourist destinations.
Keywords: consumer behavior; marketing; tourist destination; management; Ecuador